Career movement of graduates of UPV master's program (1976-1986) - Tayo, Gilma T.; Zapanta, Lea S. (Miagao, Iloilo University of the Philippines in the Visayas, 1989)
To assess the relevance and effectiveness of UPV graduate program in terms of career mobility of its graduates, questionnaires were mailed to UPV master's degree graduates of 1976 up to the present. From 233 responses it was shown that 70% were promoted after acquiring their master's degrees. The respondents considered degree as the major factor for their ppromotion, followed by work attitude and intelligence. Of those that were given priority of promotion over other master's degree holders in their companies, 59% believed their UP degree gave them the edge.
[Research Paper] -- Iloilo City : U.P. in the Visayas, May 1989 .
Keywords: UPV master's program graduates -- 1976-1986 -- Career movement